The Influence of the Audit Committee and External Audit on the Quality of Financial Reports in Manufacturing Companies - Evi Dora Sembiring; Deti Susilawati; Firli Agusetiawan Shavab Firli (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to analyze the effect of the audit committee and the external audit on the quality of financial statements. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the chemical sub-sector for the period 2018-2021. The data used in this study is secondary data, which comes from the annual report. The sampling technique used is purposive sampling with the number of companies as many as 12 times 4 periods to 48 sample data. Methods of data analysis using SPSS version 26 program, namely descriptive statistics, classical assumption test and multiple regression analysis. The results of this study indicate that partially the Audit Committee has a significant negative effect on the quality of financial reports and External Audit has a positive effect on the quality of reports. Simultaneously, the audit committee and the External Audit have an effect on the quality of financial reports.